Motivation as Mediation for the Relationship between Situational Leadership Style, Organizational Culture, and Work Environment on Employee Performance at IZI Surabaya Branch Office - Sukarno, Gendut; Rosmawati, Lisma (Formosa Journal of Multidisciplinary Research, 2024)
This study looks at how organizational culture, work environment, and situational leadership style affect employee motivation at the IZI Surabaya Branch Office and performance. Partial Least Square (PLS) was utilized in the quantitative analysis of the data, which involved a saturated sample of 35 employees. The findings demonstrate that, in contrast to organizational culture, situational leadership style and work environment have a direct impact on employee performance. The study also discovered that there was no significant effect of the three variables' indirect effects on employee performance through motivation. These results highlight the significance of work environment and leadership elements in enhancing performance, but they also imply that motivation's function as a mediator may have less of an impact in this particular organizational setting.